THE EFFECT OF KNOWLEDGE ABOUT ADOLESCENT REPRODUCTIVE HEALTH ON PRE MARITAL SEXUAL BEHAVIOUR IN INDONESIA - Sri Lilestina Nasution (Widyariset, 2012)
The objective of this study is to identify the effect of knowledge about adolescent reproductive health andsexual behaviour before marriage to marriage among adolescents in Indonesia. This study uses secondary datafrom the Youth Development Plan performance indicators survey conducted in 33 provinces in Indonesia. Thenumber of sample of this survey was 23,619 respondents conducted on adolescent women and men with an agelimit between 15–24 years. Units of samples used in the analysis of all unmarried women and men. This researchis an explanatory research which is multiple regression analysis. The use of multiple regression analysis is to testthe effect of independent variables on the dependent variable. The findings of this study demonstrate knowledgeof reproductive health influencing on sexual behaviour in adolescents in Indonesia. The findings of the studyindicate that the variable of reproductive health knowledge is a variable that affects significantly pre maritalsexual behaviour.